Parâmetros radiográficos de displasia coxofemoral na raça Rottweiler - P.C. Genuíno; F.G. Miranda; C.M.F. Rezende; R.C.S. Tôrres (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2015)
In this study, 139 radiographs of the Rottweiller breed dog, 44 males and 95 females were evaluated. Radiographs were classified by the degree of hip dysplasia, and we measured the angle of inclination, Norberg angle, the cortical index and percentage of coverage of the femoral head on both sides. The aim of this study was to evaluate that parameters based on gender and age of animals correlating them with the incidence and severity of hip dysplasia. In dysplastic dogs the mean Norberg angle was 100.09 ± 7.86 °, the mean percent coverage of the femoral head was 41.50 ± 8.59%, the mean femoral cortical index was 0.33 ± 0.04, and the femoral angle mean was 153.06 ± 9.81 °. Higher inclination angles were associated with smaller angles of Norberg and lowest percentage of coverage of the femoral head. In this study gender, cortical index and angle of inclination did not show any association with the DCF.